Monoaminergic balances predict non-depression-like phenotype in Learned Helplessness Paradigm. (1st August 2020) - Muneoka, Katsumasa; Oda, Yasunori; Iwata, Masaaki; Iyo, Masaomi; Hashimoto, Kenji; Shirayama, Yukihiko
Highlights: Learned helplessness was investigated to explore mechanisms of stress resilience and therapeutic targets for depression. Stress resilience is linked to low noradrenergic activity in the amygdala and high serotonergic activity in the nucleus accumbens. Therapeutic targets are dopaminergic activity reduction in the hippocampus and orbitofrontal cortex, and elevation in the amygdala. Further targets are facilitation of 5-HT activity in the hippocampus, medial prefrontal cortex, and nucleus accumbens. Abstract: Monoamine neuronal system abnormality is hypothesized to be the neurochemical pathology in depression, as it is supported by the efficacy of conventional antidepressants. The learned helplessness paradigm generates depression-like (LH) and non-depression-like (non-LH) behavioral models. Examination of the neurochemical states accompanying such distinct behavioral phenotypes can facilitate investigations of the mechanisms underlying resilience and the search for new strategies for depression prevention and therapy. Here, we measured the levels of monoamines, including noradrenaline (NA), serotonin (5-HT), and dopamine (DA), and their metabolites in the medial prefrontal cortex (mPFC), orbitofrontal cortex (OFC), hippocampus, nucleus accumbens (NAc), amygdala, and striatum in LH, non-LH, and non-manipulated (naïve) rats. Compared with LH rats, non-LH rats showed lower 3-methoxy-4-hydroxyphenylglycol (MHPG) levels and NA turnovers in the amygdala and higher 5-HT levels in the NAc. Compared with naïve rats, non-LH rats showed increased DA and homovanillic acid (HVA) levels in the amygdala and increased 5-hydroxyindoleacetic acid (5-HIAA) levels in the hippocampus and NAc, whereas LH rats exhibited increased HVA levels and DA turnovers in the hippocampus, decreased 5-HIAA levels in the mPFC, increased DA turnovers in the OFC, and decreased DA turnovers in the amygdala. Comparison between LH and non-LH suggest that suppressed amygdaloid NA activity and elevated 5-HT activity in the NAc are related to stress resilience. Changes that occurred in LH or non-LH rats when compared with those in naïve rats suggest that suppressed DA activity in the hippocampus and OFC; elevated DA activity in the amygdala; and facilitated 5-HT activity in the hippocampus, mPFC, and NAc are phenomena related to the expression of a non-depression-like phenotype.